3(x-2)-3=-3(-6x+9)-7x

Simple and best practice solution for 3(x-2)-3=-3(-6x+9)-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)-3=-3(-6x+9)-7x equation:



3(x-2)-3=-3(-6x+9)-7x
We move all terms to the left:
3(x-2)-3-(-3(-6x+9)-7x)=0
We multiply parentheses
3x-(-3(-6x+9)-7x)-6-3=0
We calculate terms in parentheses: -(-3(-6x+9)-7x), so:
-3(-6x+9)-7x
We add all the numbers together, and all the variables
-7x-3(-6x+9)
We multiply parentheses
-7x+18x-27
We add all the numbers together, and all the variables
11x-27
Back to the equation:
-(11x-27)
We add all the numbers together, and all the variables
3x-(11x-27)-9=0
We get rid of parentheses
3x-11x+27-9=0
We add all the numbers together, and all the variables
-8x+18=0
We move all terms containing x to the left, all other terms to the right
-8x=-18
x=-18/-8
x=2+1/4

See similar equations:

| g+62=373 | | v-6=-25 | | 8g=880 | | 3k=309 | | 3k=209 | | g-67=397 | | 4.94-0.08x=3.42 | | g−67=397 | | 4.9t^2+40t/600=0 | | 8p=680 | | 6x+42=-8(x-7) | | p2-12=-4p | | p/19=28 | | h+219=952 | | 594=27j | | 25+12x=-11 | | v/19=22 | | h/9=4 | | -5v+2(v+5)=-8 | | q=561=975 | | 43=8c-5- | | t+406=505 | | -6x-5=6x+91 | | j+2=86 | | 70+6x+14+5x+14x+1=360 | | 13=j-10 | | -18=-12+m | | -5-8c=43 | | 82=m+16 | | 7x+6=-x+38 | | -9=n-2 | | 2/5(1/2y+5)-4/5=1/2y-1+10y |

Equations solver categories